2022
DOI: 10.1039/d2cc01226j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights of molecular metal polyselenides for catalytic hydrogen generation

Abstract: Molecular metal chalcogenides have attracted great attention as electrocatalysts for the hydrogen evolution reaction (HER). However, efficient utilisation of the active sites and catalytic performance modulation has been challenging. Here...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The difference in electronegativity of sulphur and selenium is smaller, however it is still large enough to manifest as a 0.1 V difference in the standard reduction potential of the E/E 2− couple [24] . It is further observed that structures containing the [Mo V 2 (μ‐O) 2 O 2 ] 2+ motif are invariably supported by negatively charged ligands [1, 25–29] coordinated to the axial position, whilst the [Mo V 2 (μ‐S) 2 O 2 ] 2+ and [Mo V 2 (μ‐Se) 2 O 2 ] 2+ are found supported by water [30, 31] on their axial positions, or with uncoordinated axial positions [32, 33, 34] …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The difference in electronegativity of sulphur and selenium is smaller, however it is still large enough to manifest as a 0.1 V difference in the standard reduction potential of the E/E 2− couple [24] . It is further observed that structures containing the [Mo V 2 (μ‐O) 2 O 2 ] 2+ motif are invariably supported by negatively charged ligands [1, 25–29] coordinated to the axial position, whilst the [Mo V 2 (μ‐S) 2 O 2 ] 2+ and [Mo V 2 (μ‐Se) 2 O 2 ] 2+ are found supported by water [30, 31] on their axial positions, or with uncoordinated axial positions [32, 33, 34] …”
Section: Resultsmentioning
confidence: 98%
“… [24] It is further observed that structures containing the [Mo V 2 (μ‐O) 2 O 2 ] 2+ motif are invariably supported by negatively charged ligands[ 1 , 25 , 26 , 27 , 28 , 29 ] coordinated to the axial position, whilst the [Mo V 2 (μ‐S) 2 O 2 ] 2+ and [Mo V 2 (μ‐Se) 2 O 2 ] 2+ are found supported by water[ 30 , 31 ] on their axial positions, or with uncoordinated axial positions. [ 32 , 33 , 34 ]…”
Section: Resultsmentioning
confidence: 99%
“…This includes research on other types of thiometalates, such as thiotungstates, [ 33 ] mixed‐ligand clusters, e.g., featuring oxo‐ or organic ligands in addition to thio groups, [ 17 ] as well as selenide‐containing derivatives. [ 110 ] While these areas are highly promising, they have thus far not received the attention to allow us to draw any final conclusions on the component suitability for HER studies.…”
Section: Discussionmentioning
confidence: 99%
“…[24] It is further observed that structures containing the [Mo V 2 (μ-O) 2 O 2 ] 2 + motif are invariably supported by negatively charged ligands [1,[25][26][27][28][29] coordinated to the axial position, whilst the [Mo V 2 (μ-S) 2 O 2 ] 2 + and [Mo V 2 (μ-Se) 2 O 2 ] 2 + are found supported by water [30,31] on their axial positions, or with uncoordinated axial positions. [32,33,34]…”
Section: Forschungsartikelmentioning
confidence: 99%